2021
DOI: 10.15585/mmwr.mm7002e2
|View full text |Cite
|
Sign up to set email alerts
|

Rates of COVID-19 Among Residents and Staff Members in Nursing Homes — United States, May 25–November 22, 2020

Abstract: On January 8, 2021, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).During the beginning of the coronavirus disease 2019 (COVID-19) pandemic, nursing homes were identified as congregate settings at high risk for outbreaks of 2). Their residents also are at higher risk than the general population for morbidity and mortality associated with infection with SARS-CoV-2, the virus that causes COVID-19, in light of the association of severe outcomes with older age and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
114
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 6 publications
7
114
4
1
Order By: Relevance
“…A national US study of COVID-19 rates over time among nursing home HCWs observed that these incidence data paralleled community trends. 8 The Toronto-based analysis cited previously also showed the HCW rates paralleled and even preceded wider population trends. 1 …”
Section: Discussionmentioning
confidence: 73%
“…A national US study of COVID-19 rates over time among nursing home HCWs observed that these incidence data paralleled community trends. 8 The Toronto-based analysis cited previously also showed the HCW rates paralleled and even preceded wider population trends. 1 …”
Section: Discussionmentioning
confidence: 73%
“…Data on residents were abstracted starting on the date of their SNF's first vaccination clinic or their admission into the facility, whichever occurred later. Electronic medical record data included demographic characteristics, facility admission and discharge dates, vaccination dates, symptoms of COVID-19 occurring within 7 days before or 14 days after a positive test result, presence of underlying medical conditions associated with potential increased risk for severe COVID-19 illness, ¶ 1 ; Gordana Derado, PhD 1 ; Jennifer R. Verani, MD 1 ; Stephanie J. Schrag, DPhil 1 ; John A. Jernigan, MD 1 ; Vivian H. Leung, MD 3, † ; Sunil Parikh, MD 4, † and death. SARS-CoV-2 test dates, test types, and results were also obtained from the electronic medical record.…”
mentioning
confidence: 99%
“…Residents and staff members of long-term care facilities (LTCFs), because they live and work in congregate settings, are at increased risk for infection with SARS-CoV-2, the virus that causes coronavirus disease 2019 (COVID-19) (1,2). In particular, skilled nursing facilities (SNFs), LTCFs that provide skilled nursing care and rehabilitation services for persons with complex medical needs, have been documented settings of COVID-19 outbreaks (3).…”
mentioning
confidence: 99%